2009
DOI: 10.1007/s11746-009-1478-0
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Lipase‐Catalyzed Alcoholysis of Sunflower Oil: Effect of Phase‐Equilibrium on Process Efficiency

Abstract: Phase-equilibrium diagrams of biodiesel synthesis substrate (oil/alcohol/alkyl esters) and product (alkyl esters/glycerol/alcohol) mixtures containing methanol, ethanol and propanol, respectively, were used for the identification of those composition ratios leading to mixture homogeneity. Based on the diagrams, complete conversion of the substrate oil contained in a sunflower oil/ ethanol/ethyl ester mixture at a weight ratio of 7.6:11.4:81.0 resulted in the generation of an amount of glycerol capable of remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…In the studies in which a single lipase was employed, the results obtained showed high reaction yield. 40,43,44 However, the operating times were, in general, lower than the one obtained in the current research.…”
Section: Operational Stability Of Combi-lipases In a Continuous Packecontrasting
confidence: 77%
“…In the studies in which a single lipase was employed, the results obtained showed high reaction yield. 40,43,44 However, the operating times were, in general, lower than the one obtained in the current research.…”
Section: Operational Stability Of Combi-lipases In a Continuous Packecontrasting
confidence: 77%
“…Considering these drawbacks, several studies suggest the use of lipases for enzymatic transesterification of triglycerides as an interesting alternative to the alkaline process . Compared to the conventional reaction of biodiesel production, the enzymatic route is considered a “greener reaction” due to its environmental benefits, since there is no generation of alkaline wastewater, as well as washing steps for catalyst removal being unnecessary . In addition, this technology has benefits such as production of a high purity biodiesel, easy separation of products and byproducts from the reaction, mild reaction conditions of temperature and pressure, and production of a glycerin with minimum content of contamination by the catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to the lower amount of undissolved alcohol in the substrate when we use ethanol than methanol because it is much amount of undissolved alcohol that inhibits the enzyme activity [57]. Thus, since ethanol is more soluble in oil than methanol [58], enzyme inhibition effect is very low when we use ethanol than methanol. Cervero' et al [25] also indicated that at maximum reaction time, the conversion of soybean oil to biodiesel was almost similar for both single step and multiple step addition of ethanol to the reaction.…”
Section: Technology Option Imentioning
confidence: 99%